Strengthening vaccine uptake: a qualitative assessment of community health worker educational resource needs and community perspectives on vaccination in Western Kenya - Job, Nophiwe; M’pfunya, Sei-kashe; Mudhune, Sandra; Nyawade, Benson; Omondi, George; Edelquinn, Mumma; Sadia, Moses; Odhiambo, Erick K.; Ho, Xian; Skinner, Nadine; Johnston, Jamie Sewan; Ward, Victoria; et al. (Frontiers in Public Health, 2025)
IntroductionVaccination strengthens health systems by preventing the spread of infectious diseases and reducing morbidity and mortality. The introduction of the malaria vaccine in Kenya, alongside the growing access to technological tools, offers a timely opportunity to explore the educational needs of community health workers (CHWs) and the feasibility of digital training and health education resources for CHWs.MethodsA qualitative descriptive study was conducted among CHWs and community members in two sub-counties in Migori County. In-depth interviews were held with 20 CHWs selected through stratified random sampling from 72 community health units grouped into eight strata. Additionally, four focus group discussions were conducted with 32 community members. Thematic analysis was conducted using both inductive and deductive coding approaches.ResultsCHWs strongly preferred in-person training with visual aids but showed cautious interest in digital learning tools. Key barriers to digital training include limited digital literacy, language constraints, smartphone access, and associated costs. Community members supported vaccination and trusted CHWs due to their training and affiliation with health facilities. However, vaccine hesitancy persists, driven by fears of side effects, cultural beliefs, and misinformation. Confusion surrounding the limited geographic rollout of the malaria vaccine has contributed to skepticism, with some misinformation linking the vaccine to family planning and other health risks.DiscussionA comprehensive, community-centred communication strategy addressing the geographic rollout of the malaria vaccine is necessary. Overcoming the ‘digital divide’ through targeted training, improved technology infrastructure, and user-friendly technology may enhance CHWs’ capacity to deliver effective vaccine education within communities.